Exploring Doctors’ Willingness of Providing Service on COVID 19: A Case Study in Bangladesh - Bristy, Sayeda Kamrunnahar; Hasan, Kamrul; Haque, Muhammad Ariful; Habiba, Umme (Journal of Epidemiology and Public Health, 2021)
Background: Doctors were doing the hardest to deal with COVID-19 emergency medication deliberately when Bangladesh experienced doctors’ shortage along with a high mortality rate for